Rockburst characteristics and microseismic monitoring of deep-buried tunnels for Jinping II Hydropower Station. (June 2015) - Ma, T.H.; Tang, C.A.; Tang, L.X.; Zhang, W.D.; Wang, L.
Graphical abstract: Abstract: Generally, there is a seismogenic process before rockbursts occurrence, accompanied by formation of a great amount of micro-cracks and release of micro-seismic energy (micro-seismic precursor). The micro-seismic precursory information can be captured by micro-seismic monitoring equipment. As the micro-seismic activities are of temporal priority and spatial consistency with rockbursts events, the rockburst-prone zone can be predicted accurately. Firstly, Based on the great number of rockbursts events recorded during construction of the headrace tunnels of Jinping II Hydropower Station, the characteristics and mechanism of rockbursts and the role of geological structures are summarized in this essay. And a method was presented that the micro-seismic monitoring technology was employed in rockburst monitoring and early warning during construction of the deep-buried headrace tunnels. Full-time continuous monitoring of micro-seismic activities was realized. Comparison analysis was conducted between the rockbursts and microseismic monitoring results according to the site condition. The relationship between the spatial and temporal evolution of microseismic activities and rockbursts was revealed. The rockbursts analysis, monitoring and early warning practices indicate that: In deep-buried rock tunnels, the tempo-spatial distribution of rockbursts and rockburst intensity follow a certain law. A certain correlation exists between the occurrence of rockbursts and the influencing factors, such as the geological structure, construction method, and excavation disturbance, among which the geological structure plays a crucial role. The engineering practices in this study have proven that application of the microseismic monitoring technology in rockburst monitoring and early warning for deep-buried rock tunnels is feasible and the results are reasonably accurate, which changes the traditional viewpoint that the rockburst is unpredictable. The study in this essay provides a new research idea in rockburst prediction and safe construction for tunnels.